(untitled) (Abhat Journal, 2023)
The Ghaznavid State is a Turkish Islamic state that ruled Transoxiana, Khurasan and northern India, and made its capital the city of Ghazni. From the consolidation of the feet of Muslims in India as a belief, history and civilization, and it continued to rule it for more than two centuries until it finally fell at the hands of the Ghureen in the year 582 AH / 1186 AD. The Ghaznavid state was linked to the Abbasid Caliphate by strong ties based on solidarity and synergy. The Gaznazvid sultans were keen to establish sermons for the Abbasid caliphs, and to engrave their names on the coin. They were also keen on an official tradition represented in obtaining recognition by the Abbasid caliphs for their rule, in order to imbue their rulers with legal character, and to gain them prestige in the hearts of their subjects. The features of governance and administration systems are manifested in the ruling body represented by the Sultan, the source of rule and authority in the state, and the holders of high positions of senior statesmen who have sufficient experience and confidence, such as the minister, the governor of the region, the judge, the bailiff, the agent of the court, the supervisor and the chief of police. These are a specific specialization that he implements, assisted by a number of employees, each in his specialization